1971
DOI: 10.1103/physreva.4.957
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Experimental Differential Elastic Scattering Cross Section forH++ Ne

Abstract: 95'7electron's energy are not accounted for in the model. These would be expected to be larger for the smaller nuclei. A more detailed examination of the formulation is required to see if one can retain the basic simplicity of the impulse model and obtain corrections for these effects. publication with the understanding that no limitation shall exist on the reproduction and distribution of its published or unpublished form in whole or in part for any purpose of the U. S. Government.The result of a differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The derivation of equation (1) starts by differentiating equation (4) for A = A n with respect to E [2, p: 104]. If the result of this operation is multiplied by ~b and subtracted from the original equation multiplied by de~dE, it is found that r d~b dr…”
Section: Formal Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The derivation of equation (1) starts by differentiating equation (4) for A = A n with respect to E [2, p: 104]. If the result of this operation is multiplied by ~b and subtracted from the original equation multiplied by de~dE, it is found that r d~b dr…”
Section: Formal Analysismentioning
confidence: 99%
“…Applications have been made to : ion-atom collisions and the inversion of elastic scattering data [3][4][5][6][7][8][9]21], electron-atom collisions [8,9], quasi-stationary states [7][8][9][10][11][12], and elastic scattering in the presence of chemical reaction [13,19,20]. Semiclassical, variational and direct numerical integration methods have also been developed for calculating the positions of Regge Poles and their residues [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we get closer to 8,, branch points 3 and 4 come too close together to allow evaluation of Equation (4) by stationary phase. Since, as Ford and Wheeler show [9], beyond 8, this rainbow contribution to oSc (8) decays exponentially, then eventually this problem dies out. Thus, beyond a certain point the rainbow region has ceased to be important and only branches 1 and 2 contribute.…”
Section: Validitymentioning
confidence: 94%
“…The second region is around the rainbow region defined by Equation (8). As we get closer to 8,, branch points 3 and 4 come too close together to allow evaluation of Equation (4) by stationary phase.…”
Section: Validitymentioning
confidence: 96%